1992
DOI: 10.1007/bf03008320
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lidocaine and human somatosensoryevoked potentials during sufentanil-isoflurane anaesthesia

Abstract: 5, 20, and 40 minutes after lidocaine were 5.17 +.-1.33, 3.76 +--1.14, and3.66 +.-0.9 txg ' d1-1, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In addition, lidocaine has been shown to possess antianflammatory properties and analgesic properties [16,21,26,27]. While lidocaine has been shown to depress the amplitude and prolong the latency of SSEPs, the SSEP waveforms were preserved and interpretable when used as part of a narcotic based anesthetic [56].…”
Section: Lidocainementioning
confidence: 99%
“…In addition, lidocaine has been shown to possess antianflammatory properties and analgesic properties [16,21,26,27]. While lidocaine has been shown to depress the amplitude and prolong the latency of SSEPs, the SSEP waveforms were preserved and interpretable when used as part of a narcotic based anesthetic [56].…”
Section: Lidocainementioning
confidence: 99%
“…Local anesthetic techniques included epidural, incisional line block, intraperitoneal (IP) block, or a combination of these techniques; six cats did not receive any local anesthetics. Lidocaine (1 mg/kg) was administered by the intravenous route in two cats during surgery due to high sympathetic tone and surgical stimulation [27]. Postoperative pain was managed using a constant rate infusion (CRI) of opioid, either fentanyl (n=22) or remifentanil (n=3), followed by buccal or intravenous buprenorphine.…”
Section: Resultsmentioning
confidence: 99%
“…8 Another 16 patients observational study found decreased amplitudes and prolonged latencies of SEPs after continuous infusion of lidocaine at 4 mg/kg/h followed by intraoperative injection of lidocaine at 3 mg/kg. 9 However, contrary to these findings, one retrospective study and one randomized crossover study have suggested that continuous infusion of 1-1.5 mg/kg/h lidocaine during surgery has no effect on SEPs and MEPs. 10,11 Whether lidocaine influences intraoperative electrophysiological monitoring, whether its effects on electrophysiological monitoring are related to drug concentration, and whether electrophysiological monitoring can accurately reflect the integrity of nerve functions under anaesthesia are still unclear, and further studies are necessary.…”
Section: Introductionmentioning
confidence: 91%
“…Journal of Pain Research 2022:15 294 believe that lidocaine can affect cell electrical activity and thus interfere with electrophysiological monitoring. In the study of Schubert et al, 9 intravenous lidocaine 3 mg/kg bolus followed by infusion at 4 mg/kg/h was injected into 16 patients undergoing abdominal or orthopaedic surgery under sufentanil-based anaesthesia, to observe its effects on SEPs. The plasma-drug concentrations of lidocaine at different time points after administration were measured.…”
Section: Dovepressmentioning
confidence: 99%